Proceedings of the 2nd International Conference of Business, Accounting and Economics, ICBAE 2020, 5 - 6 August 2020, Purwoker 2020
DOI: 10.4108/eai.5-8-2020.2301092
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Purchase Halal Cosmetics on Indonesian Women

Abstract: The purpose of this paper is to investigate the factors that influence the intention to buy halal cosmetics. This paper investigates the impact of subjective norms, attitudes, and religiosity on the intention to buy halal-certified cosmetics. The sample data used in this study were 202 respondents in Indonesia. SPSS is used to test the significance of the influence of independent variables. The test results show that attitudes, subjective norms, and religiosity have a positive and significant influence on buyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Instead, most behavioural studies related to halal products and services have discussed topics such as halal food (Alam and Sayuti, 2011; Raheem and Demirci, 2018; Amalia et al , 2020), halal cosmetics (Ahmad et al , 2015; Majid et al , 2015; Aisyah, 2016) and halal travel and tourism (Chandra, 2014; Battour and Ismail, 2016; Vargas-Sánchez and Moral-Moral, 2019). Furthermore, in the Indonesian context, studies on consumer behaviour around halal intentions are dominated by halal food products (Soesilowati, 2011; Ratanamaneichat and Rakkarn, 2013; Vanany et al , 2019), halal cosmetics (Haro, 2018; Adiba, 2019; Saifudin et al , 2020) and halal fashion (Indarti et al , 2019; Leonnard et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most behavioural studies related to halal products and services have discussed topics such as halal food (Alam and Sayuti, 2011; Raheem and Demirci, 2018; Amalia et al , 2020), halal cosmetics (Ahmad et al , 2015; Majid et al , 2015; Aisyah, 2016) and halal travel and tourism (Chandra, 2014; Battour and Ismail, 2016; Vargas-Sánchez and Moral-Moral, 2019). Furthermore, in the Indonesian context, studies on consumer behaviour around halal intentions are dominated by halal food products (Soesilowati, 2011; Ratanamaneichat and Rakkarn, 2013; Vanany et al , 2019), halal cosmetics (Haro, 2018; Adiba, 2019; Saifudin et al , 2020) and halal fashion (Indarti et al , 2019; Leonnard et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Still, they do not care too much about whether they are halal products. On the other hand, Saifudin et al (2020) reported that religiosity significantly affected Generation Y Muslim consumers' intention to choose halal cosmetic products. Haquea et al (2018) found that attitudes, perceived behavioural control, and religiosity had significant relationships with purchase intention, but that subjective norms had an insignificant relationship with it.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of halal cosmetics covers industrial practices like the utilization of halal components and resources, stored, packaged and shipped according to permits and sharia requirements according to followers of Islam (Elasrag, 2016). Sales of cosmetics have grown rapidly in the last decade because many people are starting to be interested in looking attractive and taking care of themselves, but are aware of halal cosmetics (Saifudin et al, 2020).…”
Section: Cosmetics Halalmentioning
confidence: 99%